Optimal design method with thermomagnetic field coupling analysis for miniaturization of permanent magnet synchronous motor. Issue 2 (24th January 2013) - Kitamura, Hideki; Iwasaki, Norihisa; Kitamura, Masashi; Mori, Hideaki; Yamasaki, Masahide; Nihei, Hideki
Abstract A straightforward solution for minimizing the cost of major materials used in motors, such as permanent magnets and silicon steel sheets, is to reduce the motor size as far as possible. However, there is a trade‐off between the motor size and temperature rise in the motor that should be taken into account while reducing the motor size. For achieving this, we have been developing an optimal design method based on a combination of a thermomagnetic field coupling analysis and a direct search algorithm. This paper reports the details of this design method. A multipole permanent magnet synchronous motor of an outer rotor is the test motor. The results of the torque‐density‐maximization problem involving constraints on the terminal voltage, coil‐temperature rise, and demagnetization of the permanent magnet are shown. The usefulness of our method is also demonstrated. © 2013 Wiley Periodicals, Inc. Electr Eng Jpn, 183(2): 29–38, 2013; Published online in Wiley Online Library (wileyonlinelibrary.com). DOI 10.1002/eej.22346